The crooked timber of humanity : chapters in the history of ideas - Berlin, Isaiah, 1909-1997 (Princeton University Press, 2013)
""Out of the crooked timber of humanity, no straight thing was ever made.""--Immanuel Kant Isaiah Berlin was one of the most important philosophers of the twentieth century--an activist of the intellect who marshaled vast erudition and eloquence in defense of the endangered values of individual liberty and moral and political plurality. In The Crooked Timber of Humanity he exposes the links between the ideas of the past and the social and political cataclysms of our own time: between the Platonic belief in absolute truth and the lure of authoritarianism; between the eighteenth-